The relationship between violence across the life course, protective factors and mental disorders among adult women living in a slum setting in Ibadan, Nigeria - Sekoni, Olutoyin Olubunmi (My University, 2024)
Research suggests that adult women in Nigeria have experienced traumatic events (TE) across their life course. Violence is a TE that can occur within intimate relationships as well as other spheres of life. TE and adverse life events can increase risk of a mental disorder such as: depression, anxiety and Post Traumatic Stress Disorder (PTSD). Despite experience of TE or adverse life events, some women do not experience the onset of a mental disorder which may be due to protective factors such as resilience and social support. The links between lifecourse TE and the development of common mental disorders have not been well researched on the African continent particularly in slum settings. This thesis aimed to investigate the relationships between adult women’s childhood trauma, experiences of Intimate Partner Violence (IPV) and adverse life events and common mental disorders among adult women living in a slum setting in Ibadan, Nigeria. The thesis also sought to examine the presence of protective factors in these relationships. Methods -A community-based cross-sectional household survey utilizing multistage sampling was carried out among 550 women. Childhood trauma was measured using the short form of the Childhood Trauma Questionnaire. IPV was measured using the WHO Multi-country Study on Women's Health and Domestic Violence Questionnaire. Common mental disorders were measured using the short version of the Depression, Anxiety and Stress Scale (DASS-21) while the Harvard Trauma Questionnaire was used to measure PTSD. Recent stressors were measured using the Life Events Questionnaire. The protective factors of resilience, social support, social connectedness and self- esteem were measured using the Wagnild and Young resilience scale, the Multidimensional Scale of Perceived Social Support, the Social Connectedness Scale (Revised) and the Rosenberg self-esteem scale respectively. Bivariate and multivariate analysis were conducted to identify any associations and net effect of the key independent variables on the primary outcomes of interest while controlling for socio demographic characteristics. Results The prevalence of lifetime and past year experience of IPV were 31.5% and 14.8% respectively. The prevalence of the TE during childhood ranged from 8.9% (sexual abuse), 50.4% physical abuse and 70.4% emotional abuse, while 30.8%, 41.6% and 5.8% had experienced one, two and three forms of childhood trauma respectively. Women who had experienced all three forms of childhood trauma had five times the odds of reporting a lifetime experience of IPV compared to those who had not had any experience of childhood trauma (OR= 5.21; CI= 2.30-11.76). Common mental disorders were reported by 14.0% of the respondents, with PTSD reported by 4.18%. Resilience and social support were found to be protective against reporting symptoms of common mental disorders. Women who reported higher levels of social support and resilience were less likely to report common mental disorders (OR:0.96, 95% CI 0.93, 0.98) and (OR:0.95, 95% CI 0.91, 0.99) respectively. Women who were 65 years and older were also less likely to report the occurrence of common mental disorders (OR:0.38, 95% CI 0.15, 0.98) compared to those aged 18–34 years. Conclusion- The findings from this study show that trauma over the life course is prevalent among the women in these slums as a result of childhood trauma, IPV and recent stressors. The findings also show that even though many of the women were exposed to trauma, most of them did not develop mental disorders. Resilience and social support appeared to play an important role in mitigating the effects of adversity among this population of women even in the light of their extant circumstances within the slum setting. Addressing the use of both child protection programs and IPV reduction as well as fostering resilience and social support among women would be of benefit in reducing the burden of common mental disorders.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2023
Keywords: Mental disorders; Lifecourse; Violence; Protective factors; SDG-3: Good health and well-being; SDG-10: Reduced inequalities